Enfisema lobar infantil - Hernández González, Abdo; del Cueto Espinosa, Héctor; Díaz Sarduy, Juan A.; Acosta Tieles, Néstor (Revista Cubana de Pediatría, 2023)
Entidad clínica que constituye urgencia quirúrgica